Implementasi UU No. 18 Tahun 2012 Terhadap Peran Dinas Ketahanan Pangan Dan Pertanian Dalam Meningkatkan Kesejahteraan Petani Di Desa Kedung Dalem Kecamatan Dringu Kabupaten Probolinggo - Supriyanto; Andhi Nur Rahmadii; Moch. Nurcholis alvin (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2024)
Agriculture and food security are two important aspects in state development, which do not only focus on meeting people's food needs, but also on improving the welfare of the main actors, namely farmers. To optimize these two aspects, the Indonesian government issued Law no. 18 of 2012 concerning Food. This law provides the legal basis for implementing policies aimed at improving food security and farmer welfare. Food is one of the places to develop District Government Policy in supporting food availability, and what innovations have been implemented by the Kedung Dalem Village government in advancing the food sector in its village. It is hoped that Village Government policies can provide new innovations, or new ideas that are able to provide progress for food in developing the food sector. Kedung Dalem Village was chosen as the research location because it has quite large agricultural potential and represents the real problems faced by farmers at the local level. A deep understanding of food law enforcement at the village level is key to designing policies that are more effective and responsive to farmers' needs.